Pengembangan Sistem Firewall Adaptif Berbasis DNS untuk Memblokir Situs Pornografi di Jaringan IDN Boarding School - Hazrul Aswad; Yuma Akbar; Muhamad Umar Hasan Asrori; Fatkul Toriq (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
The fast development of information technology has improved internet availability but also raised exposure to dangerous material, especially pornography. Maintaining a safe online environment for students and the community at large is a challenge for IDN Boarding School. This study develops an adaptive firewall system using Pi-hole and DNS filtering, designed to block access to pornographic websites while preserving academic access. The system was tested through controlled network simulations involving 1000 domain requests, with results showing a 95% success rate in blocking unwanted content. The study adopts a rule-based design approach and includes usability testing with administrators. Findings suggest that integrating DNS-level filtering effectively reduces exposure to harmful content while maintaining internet stability. This research provides a scalable model for educational institutions seeking to enhance digital safety and responsible internet use.